Comparison of three office blood pressure measurement techniques and their effect on hypertension prevalence in the general population - Wohlfahrt, Peter; Cífková, Renata; Krajčoviechová, Alena; Šulc, Pavel; Bruthans, Jan; Linhart, Aleš; Filipovský, Jan; Mayer, Otto; Widimský, Jiří (Journal of hypertension, 2020)
OBJECTIVES: There is an ongoing controversy about the magnitude of the difference between unattended automated office blood pressure (AOBP) and conventional office blood pressure (BP). The aim of our study was to compare unattended AOBP with both auscultatory BP and oscillometric attended AOBP in an epidemiological setting. METHODS: In 2588 participants of the Czech post-MoNItoring of CArdiovascular Disease study (a randomly selected 1% representative population sample aged 25-64 years, mean age 48 ± 11 years, 47.5% males), BP was measured using an AOBP device unattended, auscultatory mercury sphygmomanometer and an oscillometric attended AOBP device. RESULTS: On average, auscultatory BP was 10.6/5.6 mmHg higher than unattended AOBP. Similarly, oscillometric attended AOBP was 9.9/3.4 mmHg higher than unattended AOBP, while the mean difference between attended oscillometric AOBP and auscultatory BP was 0.8/2.1 mmHg. Unattended systolic AOBP of 127 mmHg corresponded to SBP of 140 mmHg measured by a conventional sphygmomanometer. The prevalence of hypertension varied depending on the measurement technique and ranged from 31.5 to 40.1%. Reasonable agreement in hypertension diagnosis was observed with unattended AOBP cut-off at least 130/85 mmHg when compared with both auscultatory (McNemar P = 0.07, kappa 0.819) and attended oscillometric AOBP (McNemar P = 0.46, kappa 0.852) thresholds of at least 140/90 mmHg. CONCLUSION: Unattended automated office SBP is on average 10 mmHg lower than the office auscultatory or attended AOBP values. In epidemiological settings, a threshold of unattended AOBP at least 130/85 mmHg should make comparison of hypertension prevalence possible with studies using auscultatory techniques and cut-off values of 140/90 mmHg.
Keywords: dospělí; sfygmomanometry; hypertenze; Female; Prevalence; Adult; ženské pohlaví; lidé; krevní tlak; Sphygmomanometers; prevalence; Hypertension; Male; Blood Pressure Determination; měření krevního tlaku; lidé středního věku; mužské pohlaví; Blood Pressure; Middle Aged; Humans